2015
DOI: 10.1002/adhm.201500383
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Cell‐Compatible Paper Chips for Cell Culturing, Drug Screening, and Mass Spectrometric Sensing

Abstract: Paper-supported cell culture is an unprecedented development for advanced bioassays. This study reports a strategy for in vitro engineering of cell-compatible paper chips that allow for adherent cell culture, quantitative assessment of drug efficiency, and label-free sensing of intracellular molecules via paper spray mass spectrometry. The polycarbonate paper is employed as an excellent alternative bioscaffold for cell distribution, adhesion, and growth, as well as allowing for fluorescence imaging without lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Thus, these structures are a promising in vitro liver model for high-throughput drug screening assays. 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, these structures are a promising in vitro liver model for high-throughput drug screening assays. 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Although we visualized the trapped C. elegans by using the GFP (Figure 2b), the opacity of paper did not let much light pass through and did not provide high-resolution images in 3D. To enable direct and visual observation, we used paper-like transparent polycarbonate substrates for the culture system [19]. The system used the multi-laminate structure of the substrates to mimic the worm's in vivo 3D environment.…”
Section: Transparent 3d Culture Systems For C Elegansmentioning
confidence: 99%
“…Chen et al adapted the polycarbonate paper scaffold to overcome the limitations of conventional papers, such as light scattering, roughness, and low adhesion of cells . They showed that cells are well attached to the surface of the polycarbonate papers and imaged cells clearly with a bright field microscope.…”
Section: Microphysiological Models Of Human Cancermentioning
confidence: 99%